Neutrophils recruited by CXCR1/2 signalling mediate post‐incisional pain. (7th November 2012) - Carreira, E.U.; Carregaro, V.; Teixeira, M.M.; Moriconi, A.; Aramini, A.; Verri, W.A.; Ferreira, S.H.; Cunha, F.Q.; Cunha, T.M.
Abstract Background Neutrophil recruitment mediated by the CXCL1/KC chemokine and its receptors CXCR1/CXCR2 plays a critical role in inflammatory diseases. Recently, neutrophil migration and activation triggered by CXCL1‐CXCR1/2 signalling was implicated in inflammatory nociception; however, their role in post‐surgical pain has not been elucidated. In this study, we addressed the function of neutrophils in the genesis of post‐incisional pain in an experimental model of post‐surgical pain. Methods Mechanical hyperalgesia was determined with an electronic von Frey test in a mouse hindpaw incisional model. Neutrophil accumulation and the level of CXCL1/KC in the plantar tissue were determined by myeloperoxidase activity assay and enzyme‐linked immunosorbent assay, respectively. Results An incision in the mouse hindpaw produces long‐lasting mechanical hyperalgesia that persists for at least 72 h after surgery. Following surgery, there was an increase in both neutrophil accumulation and the CXCL1/KC level in the incised paws. The depletion of the mouse neutrophils by vinblastine sulphate or anti‐neutrophil antibody treatments reduced the mechanical hyperalgesia after paw incision. Furthermore, the treatment of mice with ladarixin, an orally acting CXCR1/2 antagonist, also reduced both the mechanical hyperalgesia and the infiltration of neutrophils in the incised paws. Conclusion In conclusion, it appears that after surgical processes, neutrophils are recruited by CXCL1‐CXCR1/2 signalling and participate in the cascade of events, leading to mechanical hyperalgesia. These results suggest that blocking neutrophil migration through the inhibition of CXCL1‐CXCR1/2 signalling might be a target to control post‐surgical pain.